Iman Kristen di Tengah Tantangan Pluralisme Agama [Christian Faith Amidst the Challenge of Religious Pluralism] - Daniel Winardi (Universitas Pelita Harapan, 2021)
This paper intends to study religious pluralism that is growing rapidly in this era, as a rejection to Christianity values which emphasizes Christ as the only truth. Religious pluralism that is understood as an acknowledgement of the existence of religious diversity, is shifting to the understanding that salvation must also be acknowledged in all religions and no religion can claim that they are normative or superior to other religions. The response of Christian faith in this challenging situation is by using a perspective from the doctrine of the Trinity that contains unity and plurality, that implicates Christians to always coexist in unity as fellow human beings created by God without compromising their beliefs. Christians must also do their calling by engaging in dialogue, doing apologetics, and sharing the gospel in a good and right way that is based on Christ’s love to other religious communities.